Genomic Introgression Between Critically Endangered and Stable Species of Darwin's Tree Finches on the Galapagos Islands - Rachael Y. Dudaniec; Sonu Yadav; Julian Catchen; Sonia Kleindorfer (Evolutionary Applications)
ABSTRACT Natural hybridisation among rare or endangered species and stable congenerics is increasingly topical for the conservation of species‐level diversity under anthropogenic impacts. Evidence for beneficial genes being introgressed into or selected for in hybrids raises concurrent questions about its evolutionary significance. In Darwin's tree finches on the island of Floreana (Galapagos Islands, Ecuador), the Critically Endangered medium tree finch (Camarhynchus pauper) undergoes introgression with the stable small tree finch (Camarhynchus parvulus), and hybrids regularly backcross with C. parvulus. Earlier studies in 2005–2013 documented an increase in the frequency of Camarhynchus hybridisation on Floreana using field‐based and microsatellite data. With single nucleotide polymorphism (SNP) data from the same Floreana tree finches sampled in 2005 and 2013 (n = 95), we examine genome‐wide divergence across parental and hybrid birds and evidence for selection in hybrids. We found that just 18% of previously assigned hybrid birds based on microsatellites could be assigned to hybrids using SNPs. Over half of the previously assigned hybrids (63%) were reassigned to C. parvulus, though parental species showed concordance with prior assignments. Of 4869 private alleles found in hybrid birds, 348 were at a high frequency (≥ 0.30) that exceeded their parental species of origin 89%–96% of the time. For private alleles detected in both years (N = 536) between 11%–76% of alleles underwent a frequency increase and 13%–61% a frequency decrease between 2005 and 2013, which was sensitive to sampling effort. We identified 28 private alleles that were candidates under selection via local PCA and outlier tests. Alleles were annotated to genes associated with inflammation, immunity, brain function and development. We provide evidence that introgression among a critically endangered and stable species of Darwin's tree finch across years may aid in the retention of adaptive alleles and genetic diversity in birds threatened with extinction.